Three-Random-Point Marking Method for Toric Intraocular Lens Alignment Using the iTrace Aberrometer - Yongyi Niu; Hongliang Lin; Yongjie Qin; Cheng Yang; Yanlei Chen; Jin Zeng; Hongyang Zhang (Journal of Ophthalmology)
Purpose. To evaluate the clinical outcome of the three-random-point (TRP) marking method for toric intraocular lens (IOL) alignment using the iTrace aberrometer (Tracey Technologies Corp., Houston, TX). Setting. Department of Ophthalmology, Guangdong Eye Institute, Guangdong Academy of Medical Sciences, Guangdong Provincial People’s Hospital, Guangzhou, China. Design. Prospective, randomized comparative trial. Method. Thirty eyes of 30 patients undergoing cataract surgery with coexisting corneal astigmatism of over 1.0 D were included in this study. All patients were prospectively randomized into the TRP marking group or slit-lamp horizontal meridian (SHM) marking group. TRP marking involved marking three points randomly in the corneal limbus of the patients and accurately marking the horizontal meridian was not required. The follow-up duration was 3 months after cataract surgery. Results. Fifteen eyes of 15 patients were in the TRP marking group and 15 eyes of 15 patients in the SHM marking group. There was no statistically significant difference in BCVA, UDVA, preexisting corneal astigmatism, or residual astigmatism between the groups before or after surgery P>0.05. The mean toric IOL misalignment was lesser but without significance in the TRP marking group than in the SHM marking group after 3 postoperative months (2.66° ± 1.42° versus 3.29° ± 1.67°; P=0.295). Conclusion. The TRP marking method using the iTrace aberrometer is simple and accurate for preoperative marking of toric IOLs. It can eliminate the potential systematic errors resulting from varying head positions during the preoperative keratometry measurement and from manual marking.